Reduced gene flow in a vulnerable species reflects two centuries of habitat loss and fragmentation2. Issue 2 (20th February 2018) - Stevens, Kate; Harrisson, Katherine A.; Hogan, Fiona E.; Cooke, Raylene; Clarke, Rohan H.
Abstract: Understanding the effects of landscape modification on gene flow of fauna is central to informing conservation strategies that promote functional landscape connectivity and population persistence. We explored the effects of large‐scale habitat loss and fragmentation on spatial and temporal patterns of gene flow in a threatened Australian woodland bird: the Grey‐crowned Babbler Pomatostomus temporalis . Using microsatellite data, we (1) investigated historical (i.e., pre‐fragmentation) and contemporary (i.e., post‐fragmentation) levels of gene flow among subpopulations and/or regions, (2) identified first‐generation migrants and likely dispersal events, (3) tested for signatures of genetic bottlenecks, (4) estimated contemporary and historical effective population sizes, and (5) explored the relative influences of drift and migration in shaping contemporary population structure. Results indicated that the functional connectivity of landscapes used by the Grey‐crowned Babbler is severely compromised in the study area. The proportion of individuals that were recent immigrants among all subpopulations were low. Habitat fragmentation has led to a clear division between subpopulations in the east and west, and the patterns of gene flow exchange between these two regions have changed over time. The effective population size estimates for these two regions are now well below that required for long‐term population viability ( N e < 100). Demographic history models indicate that genetic drift was a greater influence on subpopulations than gene flow, and most subpopulations show signatures of bottlenecks. Translocations to promote gene flow and boost genetic diversity in the short term and targeted habitat restoration to improve landscape functional connectivity in the long term represent promising conservation management strategies that will likely have benefits for many other woodland bird species.